Disrupted Saccade Control in Chronic Cerebral Injury: Upper Motor Neuron-Like Disinhibition in the Ocular Motor System - Rizzo, John-Ross; Hudson, Todd E.; Abdou, Andrew; Lui, Yvonne W.; Rucker, Janet C.; Raghavan, Preeti; Landy, Michael S. (Frontiers in Neurology, 2017)
Saccades rapidly direct the line of sight to targets of interest to make use of the high acuity foveal region of the retina. These fast eye movements are instrumental for scanning visual scenes, foveating targets, and, ultimately, serve to guide manual motor control, including eye-hand coordination. Cerebral injury has long been known to impair ocular motor control. Recently, it has been suggested that alterations in control may be useful as a marker for recovery. We measured eye movement control in a saccade task in subjects with chronic middle cerebral artery (MCA) stroke with both cortical and substantial basal ganglia involvement, and in healthy controls. Saccade latency distributions were bimodal, with an early peak at 60 msec (anticipatory saccades) and a later peak at 250 msec (regular saccades). Although the latencies corresponding to these peaks were the same in the two groups, there were clear differences in the size of the peaks. Classifying saccade latencies relative to the saccade ‘go signal’ into anticipatory (latencies up to 80 ms), ‘early’ (latencies between 80 and 160 ms), and ‘regular’ types (latencies longer than 160 ms), stroke subjects displayed a disproportionate number of anticipatory saccades, whereas control subjects produce the m¬¬ajority of their saccades in the regular range. We suggest that this increase in the number of anticipatory saccade events may result from a disinhibition phenomenon that manifests as an impairment in the endogenous control of ocular motor events (saccades) and interleaved fixations. These preliminary findings may help shed light on the ocular motor deficits of neurodegenerative conditions, results that may be subclinical to an examiner, but clinically significant secondary to their functional implications.